1986
DOI: 10.1056/nejm198603063141003
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, All-Cause Mortality, and Longevity of College Alumni

Abstract: We examined the physical activity and other life-style characteristics of 16,936 Harvard alumni, aged 35 to 74, for relations to rates of mortality from all causes and for influences on length of life. A total of 1413 alumni died during 12 to 16 years of follow-up (1962 to 1978). Exercise reported as walking, stair climbing, and sports play related inversely to total mortality, primarily to death due to cardiovascular or respiratory causes. Death rates declined steadily as energy expended on such activity incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
1,018
1
94

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,366 publications
(1,134 citation statements)
references
References 22 publications
21
1,018
1
94
Order By: Relevance
“…4,11,12 The American College of Sports Medicine (ACSM), for example, recommends an additional energy consumption by endurance sport on 3 days/week with a moderate intensity to prevent arteriosclerotic diseases. 13 According to the examinations by Paffenbarger et al (1986) 14 a clearly higher additional weekly energy expenditure of 2000-2500 kcal or an additional daily energy expenditure of approx. 300-350 kcal leads to the greatest possible reduction of the risk of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…4,11,12 The American College of Sports Medicine (ACSM), for example, recommends an additional energy consumption by endurance sport on 3 days/week with a moderate intensity to prevent arteriosclerotic diseases. 13 According to the examinations by Paffenbarger et al (1986) 14 a clearly higher additional weekly energy expenditure of 2000-2500 kcal or an additional daily energy expenditure of approx. 300-350 kcal leads to the greatest possible reduction of the risk of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Sports activities at this level mediate significant reductions in cardiovascular events and optimal adjustments of the cardiovascular risk profile including lipid and carbohydrate metabolism. 3,5,25 With respect to betablocking agents there is conflicting data on their suitability in the treatment of physically active patients with EH. The beneficial haemodynamic profile with marked antihypertensive effects during exercise may be counteracted by negative effects on lipid and carbohydrate metabolism as well as on exercise performance.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that running for even 5 to 10 min/d or 50 min/wk at a low speed of <6 miles/h (<10 km/h) markedly reduces the risk of death 13. However, in subgroups with the highest running intensity, the impact of running on mortality leveled off, whereas other trials even showed a loss of mortality reduction in healthy subjects and patients with CAD with high exercise intensities 10, 16, 17, 18. O′Keefe et al reviewed the pathophysiologic mechanisms of potential adverse cardiovascular effects from long‐term excessive endurance exercise, such as ultramarathons, ironman distance triathlons, or long‐distance bicycle races, which might diminish exercise‐related mortality benefits 19.…”
Section: Physical Inactivity As a Risk Factor For Cadmentioning
confidence: 99%